Medial Ankle Instability: Review of Anatomy, Evaluation, and Treatment. Issue 6 (December 2022) - Gopinath, Rohan; Pigott, Matthew; Lindsey, Benjamin; Finney, Fred T.; Holmes, James R.; Walton, David M.; Talusan, Paul G.
The medial ankle ligamentous complex, which includes the deltoid, talocalcaneal, and calcaneonavicular ligaments, functions to provide stability to the medial ankle. Injuries to the deltoid ligament can lead to medial-sided ankle pain, subsequent instability, and posttraumatic osteoarthritis given the altered biomechanics of the ankle joint. After completing a thorough physical examination, imaging modalities such as stress radiographs and magnetic resonance imaging can be used to confirm the diagnosis. Acute injuries to the deltoid ligament should be managed conservatively with a short course of immobilization. For patients with continued pain and instability following a regimen of nonoperative management, surgical intervention can be considered. Primary repair using suture anchor fixation to the medial malleolus can be utilized if sufficient tissue remains. However, if reconstruction is necessitated, autograft or allograft can be utilized in several described techniques. Levels of Evidence: Therapeutic